1995
DOI: 10.1074/jbc.270.51.30693
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Stimulation of Human Progesterone Receptor B Expression by Estrogen in T-47D Human Breast Cancer Cells

Abstract: Human progesterone receptor (PR) expression is controlled by two promoter regions giving rise to transcripts encoding PR A and B proteins. It is unknown whether estrogen and progesterone, the major physiological modulators of PR expression, exert their effects equally on the PR promoters. The aim of this study was to analyze estrogen and progestin effects on PR promoters, PR-encoding transcripts, and PR A and B proteins in T-47D human breast cancer cells. The progestin ORG 2058 caused a prolonged decrease in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 56 publications
8
67
1
2
Order By: Relevance
“…Our results also demonstrated that PRA was always equally expressed with PRB in benign proliferative lesions but sometimes dominantly expressed in IDC. These results are consistent with findings of PR isoforms in human breast tumors examined using immunoblot analysis by Graham et al 4) However, Akahira et al 27) recently demonstrated that PRB was dominantly expressed in all types or groups of epithelial ovarian carcinoma, another estrogendependent human neoplasm, using both immunohistochemistry and RT-PCR. The biological significance and/ or possible significance of PR isoforms in human estrogen-dependent neoplasms requires further investigation for clarification.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results also demonstrated that PRA was always equally expressed with PRB in benign proliferative lesions but sometimes dominantly expressed in IDC. These results are consistent with findings of PR isoforms in human breast tumors examined using immunoblot analysis by Graham et al 4) However, Akahira et al 27) recently demonstrated that PRB was dominantly expressed in all types or groups of epithelial ovarian carcinoma, another estrogendependent human neoplasm, using both immunohistochemistry and RT-PCR. The biological significance and/ or possible significance of PR isoforms in human estrogen-dependent neoplasms requires further investigation for clarification.…”
Section: Discussionsupporting
confidence: 80%
“…4) However, immunolocalization of PR isoform proteins has not been reported in detail in human breast cancer. Therefore, in this study, we first immunolocalized PRA and PRB in human breast cancer and intraductal epithelial proliferative lesions.…”
mentioning
confidence: 99%
“…Furthermore, because PRB is more transcriptionally active than PRA, tumors with a high PRA:PRB are more hormone refractive. PRB is often a stronger activator of target genes such as cyclin D1 that is overexpressed in many breast cancers (Graham et al, 1995). The role of these isoforms is indeed complex (Kariagina et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the normal breast where PR-A and PR-B are coexpressed at equal levels, breast cancers often contain aberrant PR-A:PR-B ratios, an early event in breast carcinogenesis (29). As tumors progress, frequent high A:B ratios are most often associated with loss of PR-B protein (rather than gain of PR-A) (30). In fact, PR loss is an excellent marker of heightened protein tyrosine kinase activities and tamoxifen resistance (31).…”
Section: Pr Sumoylation Favors Hdac Binding But Prevents Src1 Interacmentioning
confidence: 99%